Oncogenic Ras mutant causes the hyperactivation of NF‐κB via acceleration of its transcriptional activation - Kenji Tago; Megumi Funakoshi‐Tago; Satoshi Ohta; Hirotoshi Kawata; Hiroshi Saitoh; Hisanaga Horie; Chihiro Aoki‐Ohmura; Junji Yamauchi; Akira Tanaka; Jitsuhiro Matsugi; Ken Yanagisawa (Molecular Oncology)
It is well established that nuclear factor κB (NF‐κB) acts as one of the most important transcription factors for tumor initiation and progression, as it both protects cells from apoptotic/necrotic signals and accelerates angiogenesis and tumor metastasis, which is mediated via the expression of target genes. However, it has not yet been clarified how oncogenic signals accelerate the activation of NF‐κB. In the current study, we utilized untransformed NIH‐3T3 cells stably harboring a κB‐driven luciferase gene to show that an oncogenic mutant of Ras GTPase augmented TNFα‐induced NF‐κB activation. Notably, enforced expression of cyclin‐dependent kinase inhibitors, such as p27Kip1 and p21Cip1, effectively canceled the accelerated activation of NF‐κB, suggesting that oncogenic Ras‐induced cell cycle progression is essential for the hyperactivation of NF‐κB. Furthermore, we found that Ras (G12V) augmented the transcriptional activation of NF‐κB, and this activation required the p38 MAP kinase. We observed that a downstream kinase of p38 MAP kinase, MSK1, was activated by Ras (G12V) and catalyzed the phosphorylation of p65/RelA at Ser‐276, which is critical for its transcriptional activation. Significantly, phosphorylation of the p65/RelA subunit at Ser‐276 was elevated in patient samples of colorectal cancer harboring oncogenic mutations of the K‐Ras gene, and the expression levels of NF‐κB target genes were drastically enhanced in several cancer tissues. These observations strongly suggest that oncogenic signal‐induced acceleration of NF‐κB activation is caused by activation of the p38 MAP kinase–MSK1 signaling axis and by cell cycle progression in cancer cells.